Performance analysis of LTE codes system using various modulation techniques - Khalifa, Othman Omran (IEEE, 2021)
Modulation techniques is crucial in communications networking due to the advancement in technologies and users demands such as high data rate, low latency and good quality of services. However, to fulfil the requirements of mobile users, the Long-Term Evolution (LTE) is was introduced. It was a revolutionary step where high data rates, low latency, video chat, video conferencing and spectrum efficiency are included. However, LTE system require a powerful method to detect error and correct them. In this paper, an investigation of the performance of LTE using SC-FDMA and OFDMA with a variation in modulation techniques such as PSK, m-ary QAM based on BER and error probability were conducted.